2000
DOI: 10.1046/j.1365-2362.2000.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased antioxidant defence in individuals infected by the human immunodeficiency virus

Abstract: These results suggest that abnormalities of antioxidant defence, mainly of SOD activity, are related to the progression of the HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 38 publications
(20 reference statements)
3
53
0
4
Order By: Relevance
“…As oxidative stress in CD4 þ T cells is thought to be responsible for impaired proliferation in HIV þ patients (Roederer et al, 1992;Aukrust et al, 1995;Cayota et al, 1996;Müller et al, 2000), the increase in PHA-induced proliferation observed in group J might be explained by decreased oxidative stress in CD4 þ T cells. Owing to parallel changes of antioxidant defense in plasma and cells (Treitinger et al, 2000), a reduction of intracellular oxidative stress might have been detected indirectly by increased plasma antioxidant capacity in HIV þ subjects in group J (Arendt et al, 2001). In HIV þ patients who received the concentrate, PHA-induced proliferation did not change despite an increase in plasma Polyphenols in lymphocyte proliferation and apoptosis P Winkler et al antioxidant capacity (Arendt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As oxidative stress in CD4 þ T cells is thought to be responsible for impaired proliferation in HIV þ patients (Roederer et al, 1992;Aukrust et al, 1995;Cayota et al, 1996;Müller et al, 2000), the increase in PHA-induced proliferation observed in group J might be explained by decreased oxidative stress in CD4 þ T cells. Owing to parallel changes of antioxidant defense in plasma and cells (Treitinger et al, 2000), a reduction of intracellular oxidative stress might have been detected indirectly by increased plasma antioxidant capacity in HIV þ subjects in group J (Arendt et al, 2001). In HIV þ patients who received the concentrate, PHA-induced proliferation did not change despite an increase in plasma Polyphenols in lymphocyte proliferation and apoptosis P Winkler et al antioxidant capacity (Arendt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidation results in inactivation of antiproteases, activation of MMPs, and direct damage to the lung matrix and decreases the lung's ability to repair itself (37). HIVinfected individuals have altered systemic and lung oxidant/ antioxidant balance, with decreases in antioxidant levels such as superoxide dismutase and glutathione and increases in oxidants that may result from HIV proteins (38)(39)(40)(41). Smoking may worsen the imbalance between oxidants and antioxidants in HIV-infected persons.…”
Section: Altered Antioxidant-oxidant Balancementioning
confidence: 99%
“…Decreased antioxidant defense and increased lipid peroxidation have been described in serum from both HIV-positive individuals and AIDS patients, suggesting a disturbance of the redox equilibrium (41,42). Soluble HIV-1 trans-activator of transcription (HIV-1 Tat) has been found in supernatants of HIV-infected cells as well as in the serum of HIV-infected individuals (43)(44)(45).…”
Section: Hiv-1 Trans-activator Of Transcription Substitutes Formentioning
confidence: 99%